2008
DOI: 10.1143/apex.1.101303
|View full text |Cite
|
Sign up to set email alerts
|

Control of Domain Wall Position by Electrical Current in Structured Co/Ni Wire with Perpendicular Magnetic Anisotropy

Abstract: We report the direct observation of the current-driven domain wall (DW) motion by magnetic force microscopy in a structured Co/Ni wire with perpendicular magnetic anisotropy. The wire has notches to define the DW position. It is demonstrated that single current pulses can precisely control the DW position from notch to notch with high DW velocity of 40 m/s.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…Subsequently, it was theoretically predicted that by using perpendicular-easy-axis systems with a reduced wire thickness, the hard-axis anisotropy, which governs J th in the adiabatic regime becomes so small that a DW can be moved by the adiabatic STT at a reasonably small current density. 66,67) Following the theoretical prediction, experimental studies using a perpendicular-easy-axis Co=Ni multilayer demonstrated DW motion driven with a small current density, [68][69][70][71] as explained well by the adiabatic-STT model. 71) In this system, the independence between J th and H C was also confirmed.…”
Section: Structure and Characteristics Of Three-terminal Spintronics supporting
confidence: 57%
“…Subsequently, it was theoretically predicted that by using perpendicular-easy-axis systems with a reduced wire thickness, the hard-axis anisotropy, which governs J th in the adiabatic regime becomes so small that a DW can be moved by the adiabatic STT at a reasonably small current density. 66,67) Following the theoretical prediction, experimental studies using a perpendicular-easy-axis Co=Ni multilayer demonstrated DW motion driven with a small current density, [68][69][70][71] as explained well by the adiabatic-STT model. 71) In this system, the independence between J th and H C was also confirmed.…”
Section: Structure and Characteristics Of Three-terminal Spintronics supporting
confidence: 57%
“…Besides fundamental investigations, the use of domain walls in logic 19 and memory 20 devices has already been proposed. Low current densities and high domain wall (DW) velocities at zero magnetic field are required for future applications.Direct evidence of CIDM at zero field has been reported for several nanostripe systems, including permalloy (FeNi) 6,11 , magnetic semiconductors 9 and systems with perpendicular magnetization 7,12,14,15 . For the commonly used FeNi system, the critical current densities are not much below 10 12 A/m 2 at zero magnetic field 8,11 , associated with DW velocities going from some m/s up to about 100 m/s 11 .…”
mentioning
confidence: 99%
“…Since the prediction of spin-torque effects 2 , many experimental 3,4,5,6,7,8,9,10,11,12,13,14,15 and theoretical 16,17,18 works have been dedicated to the study of currentinduced domain wall motion (CIDM). Besides fundamental investigations, the use of domain walls in logic 19 and memory 20 devices has already been proposed.…”
mentioning
confidence: 99%
“…Each magnetic layer is assumed to be Co/Ni multilayer. 13 The stable magnetic domain wall structure in each layer can be determined by the exchange coupling strength J ex and the wire width. The exchange stiffness constant A is 1.0 × 10 −6 erg/cm, the uniaxial anisotropy constant K u is 4.0 × 10 6 erg/cm 3 , the saturation magnetization M s is 600 emu/cm 3 and the interlayer exchange coupling J ex t is varied from −0.5 erg/cm 2 to 0.5 erg/cm 2 .…”
Section: Methodsmentioning
confidence: 99%